Effect on Balance Function in Patients with Parkinson's Disease Treated by Transcranial Direct Current Stimulation - Na QIAO; Jianjun LU; Yongliang GUO; Wenhua ZHENG; Tiebin YAN (康复学报)
Objective:To observe the improvement of balance function in patients with Parkinson's disease treated by transcranial direct current stimulation(tDCS).Methods:With double-blind, random and control studies, using the random number generator in SPSS 20.0 statistical software, a total of 49 patients with Parkinson's disease who met the inclusion criteria were divided into intervention group(n=25)and control group(n=24).In addition to the routine treatment, both of groups were given the treatment of tDCS respectively. Anode electrode of tDCS was placed over the left dorsolateral prefrontal cortex, and cathode electrode of tDCS was placed over the right orbital frontal cortex. Two groups were treated once a day, 20 min per time, and for 5 consecutive days. The difference between two groups was that the current intensity of the intervention group was 2 mA, while acting as a placebo condition, the current intensity of the control group was 2 mA only at the first and last 30 s during the treatment, the rest of time was 0 mA.Before and after 5 days, patients with Parkinson's disease were evaluated by scales in terms of Berg Balance Scale(BBS)and NeuroCom Balance system(parameters including scores of balance test under six conditions).Results:Before treatment, there was no statistically significant difference between the two groups on BBS scores and the balance results of the 6 kinds of balance conditions in the NeuroCom Balance system(P>0.05).After five days'treatment, BBS scores(52.24±4.04)of the intervention group were improved compared with those(50.44±4.89)before treatment, and the difference was statistically significant(P<0.05);the BBS scores(51.96±4.11)of the control group were improved compared with those(49.75±4.74)before treatment, and the difference was statistically significant(P<0.05);there was not statistically significant in the BBS scores after treatment between the two groups(P>0.05).After five days'treatment, the evaluation values of NeuroCom Balance system of condition①, ②, ③and⑤in the intervention group were not statistically significant(P>0.05);the evaluation values of NeuroCom Balance system of condition④(73.21±8.89)and⑥(37.42±26.46)in the intervention group were statistically significant than before(64.72±13.93)and(31.09±29.28)(P<0.05).The evaluation values of NeuroCom Balance system of condition①, ②, ③, ④, ⑤and⑥in the control group were not statistically significant(P>0.05).Conclusion:tDCS could enhance the visual spatial processing and vestibular function in patients with Parkinson's disease and improve the ability with their balance.